Estimation of summer crop areas in the state of Paraná, Brazil, using multitemporal EVI/Modis images - Johann, Jerry Adriani; Rocha, Jansle Vieira; Duft, Daniel Garbellini; Lamparelli, Rubens Augusto Camargo (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to estimate and map crop areas with soybean and corn in the state of Paraná, Brazil, using EVI/Modis images. The crop seasons from 2004/2005 to 2007/2008 were evaluated. Due to the high temporal dynamics and difference in sowing dates of the cultures within the state, scenes containing the pre‑planting and initial crop development phases were used to obtain the minimum EVI image (IMIE), and scenes at the peak of the crop cycle were used to obtain the maximum EVI image (IMAE). These images were used to generate the RGB color composition (R, IMAE; GB, IMIE), which allowed for the creation of masks of the areas planted with soybean and corn. The estimation of masked areas by municipality was compared with the municipal agricultural production official data, and good fits (R²>0.84, d>0.95, c>0.85) were observed between data. For spatial accuracy assessment, Landsat‑5/TM and AWiFS/IRS images were used as references to build the error matrix. The obtained results indicate that the proposed methodology is highly efficient and may be used as a model for cropland mapping.